Lung Involvement in Primary Sjögren's Syndrome—An Under-Diagnosed Entity - Sogkas, Georgios; Hirsch, Stefanie; Olsson, Karen Maria; Hinrichs, Jan B.; Thiele, Thea; Seeliger, Tabea; Skripuletz, Thomas; Schmidt, Reinhold Ernst; Witte, Torsten; Jablonka, Alexandra; Ernst, Diana (Frontiers in Medicine, 2020)
Interstitial lung disease (ILD) represents a frequent extra-glandular manifestation of primary Sjögren’s Syndrome (pSS). Limited published data regarding phenotyping and treatment exists. Advances in managing specific ILD phenotypes have not been comprehensively explored in patients with coexisting pSS. This retrospective study aimed to phenotype lung diseases occurring in a well-described pSS cohort and describe treatment course and outcomes. Between April 2018 and February 2020, all pSS patients attending our Outpatient clinic were screened for possible lung involvement. Clinical, laboratory and computer tomography (CT) findings were analysed. Patients were classified according to CT findings into 5 groups: usual interstitial pneumonia (UIP), non-specific interstitial pneumonia (NSIP), desquamative interstitial pneumonia (DIP), combined pulmonary fibrosis and emphysema (CPFE) and unspecific-ILD. Lung involvement was confirmed in 31/68 patients (13%). ILD at pSS diagnose was present in 19/31 (61%) patients. The commonest phenotype was UIP n= 13 (4143%), followed by NSIP n=9 (29%), DIP n=2 (6 %), CPFE n=2 (6 %) and unspecific-ILD n= 5 (16%). Forced vital capacity (FVC) and carbon monoxide diffusion capacity (DLCO) appeared lower in UIP and DIP, without reaching a significant difference. Treatment focused universally on intensified immunosuppression, with 13/31 patients (42 %) receiving cyclophosphamide. No anti-fibrotic treatments were used. Follow-up was median 38.2 [12.4-119.6] months. Lung involvement in pSS is heterogeneous. Better phenotyping and tailored treatment may improve outcomes and requires further evaluation in larger prospective studies.